Adhesive Systems Used in Indirect Restorations Cementation: Review of the Literature - Cristian Abad-Coronel; Belén Naranjo; Pamela Valdiviezo (MDPI AG, 2019)
New technologies are changing the therapeutical options to do indirect restorations and new adhesive systems are continuously introduced to be used by clinicians. Different interactions between restorations, adhesive systems components, enamel and dentin require having criteria based on the selection of the adhesive system, ensuring the longevity of the restorations and the preservation of the biological remnant. The adhesion force to the dental tissue is one of the indicatives of the behavior of the adhesive systems and influences the behavior of the treatments with direct and indirect restorations. The objective of this search was to find the adhesive systems with the best results in terms of the adhesion strength of indirect restorations on the dental tissues. The search was conducted in two MEDLINE digital databases (PubMed), and the Cochrane Library with a search strategy based on the combination of MeSH (Medical Subject Headings) keywords. This systematic review used the PRISMA guide (Preferred Reporting Items for Systematic Reviews and Meta-Analysis). According to this review, the 3-step adhesive systems were the best performing and still are the gold standard for the cementing of indirect restorations. In addition, it can be concluded that self-etched adhesive systems reduce the time spent in clinical practice, however at the interface level they behave as permeable membranes more susceptible to degradation.